2017
DOI: 10.15342/ijms.v4ir.129
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Replacement for Patients with Severe Aortic Stenosis and Severe Left Ventricular Dysfunction - Mortality Risk Factors

Abstract: Severe left ventricular dysfunction increases the surgical risk of aortic valve replacement on aortic valvular stenosis. Several risk factors of hospital mortality have been reported in heterogeneous series. The aim of this study was to identify mortality risk factors of aortic valve replacement in patients with severe aortic stenosis and severe left ventricular dysfunction. To avoid biases of associated diseases, our study has been focused on isolated aortic stenosis. 46 patients, with AS and severe left vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Previous studies have shown that heart valve surgery leads to myocardial reverse remodeling of the cardiac structure and improves the functional status of patients (17,(27)(28)(29), and similar results were obtained in the present study. In the present study, preoperative and postoperative (within 48 hours and 3 months after surgery) cardiac echocardiographic measurements showed a decrease in CO in all groups compared with the preoperative period, it was considered that there was false high row due to anatomical changes before operation, and the valve anatomy was recovered after operation, when CO is true cardiac output and can accurately reflect cardiac function.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that heart valve surgery leads to myocardial reverse remodeling of the cardiac structure and improves the functional status of patients (17,(27)(28)(29), and similar results were obtained in the present study. In the present study, preoperative and postoperative (within 48 hours and 3 months after surgery) cardiac echocardiographic measurements showed a decrease in CO in all groups compared with the preoperative period, it was considered that there was false high row due to anatomical changes before operation, and the valve anatomy was recovered after operation, when CO is true cardiac output and can accurately reflect cardiac function.…”
Section: Discussionsupporting
confidence: 92%